2015
DOI: 10.18387/polibotanica.40.10
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between dominant hydrophytic species of the wetlands of western Mexico mediated by fire and nitrate concentration

Abstract: SUMMARYWetland plant community dynamics are strongly driven by abiotic factors such as nutrient levels and fire. In wetlands where invasive species are present assessing the role of abiotic factors in plant-plant interactions is fundamental for both understanding community dynamics and management. In this study the interaction between pairs of species was quantified between one non-invasive (Schoenoplectus americanus), one that can become overdominant after human disturbances (Typha domingensis) and one that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
1
0
1
Order By: Relevance
“…A pesar de lo citado, los resultados de esta investigación indican que incluso después de incendios que eliminan el dosel de especies nativas, la supervivencia y crecimiento de los fragmentos de P. australis fue muy baja. Resultados similares fueron reportados por Montejo-Mayo et al (2015).…”
Section: Discussionunclassified
“…A pesar de lo citado, los resultados de esta investigación indican que incluso después de incendios que eliminan el dosel de especies nativas, la supervivencia y crecimiento de los fragmentos de P. australis fue muy baja. Resultados similares fueron reportados por Montejo-Mayo et al (2015).…”
Section: Discussionunclassified
“…In a previous short term study of the same area before the major fires of 2009 (Escutia-Lara et al, 2009), we concluded that fires might play a positive role in maintaining plant diversity in Western Mexico wetlands. This can still be the case for low-intensity infrequent fires, that open the canopy of the obligate dominant hypdrophytes (Typha domingensis and S. americanus), and allow other natives to be present as shown by harvesting experiments in the same wetlands (Hall et al, 2008) and reducing its competitiveness (Montejo-Mayo et al, 2015). But intense and frequent fires, especially during the growing season, alter significantly the wetland plant community composition.…”
Section: Discussionmentioning
confidence: 99%